YIIFSWA II OPENDAY - Interview with Ihuoma Okwuonu - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Interview with Ihuoma Okwuonu at YIIFSWA-II Open Day at IITA Ibadan. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam.